2014
DOI: 10.1007/s00423-014-1233-3
|View full text |Cite
|
Sign up to set email alerts
|

The ill surgeon: a review of common work-related health problems amongst UK surgeons

Abstract: These occupational hazards pose a huge risk to the NHS and the personal well-being of its surgeons. As such, the importance of early awareness and education alongside prompt intervention is duly emphasized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…6,[10][11][12][13]17 High surgeon burnout rates pose significant health and safety risks for surgeons, including increased depression, diabetes mellitus, heart disease, metabolic syndrome, and myocardial infarction. 9,13,14 Burnout can also have negative effects on patient care, resulting in decreased surgeon performance and increased rates of medical errors. 16,17 Because of the detrimental effects of burnout on surgeon and patient health, the Accreditation Council for Graduate Medical Education restricted resident work hours in 2003 and 2011.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,[10][11][12][13]17 High surgeon burnout rates pose significant health and safety risks for surgeons, including increased depression, diabetes mellitus, heart disease, metabolic syndrome, and myocardial infarction. 9,13,14 Burnout can also have negative effects on patient care, resulting in decreased surgeon performance and increased rates of medical errors. 16,17 Because of the detrimental effects of burnout on surgeon and patient health, the Accreditation Council for Graduate Medical Education restricted resident work hours in 2003 and 2011.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Several studies of surgeons and nonsurgeons have found that burnout can occur at a very high rate and is increasing in prevalence; 37.9% of physicians reported burnout in 2011, and 46.9% of physicians experienced burnout in 2014. [6][7][8][9] The prevalence of burnout in orthopaedic surgeons is even higher. Reported burnout rates are as high as 65%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of problems reported by MIS surgeons varies, with most surgeons reporting neuromusculoskeletal symptoms during the MIS procedures [8] and others identifying symptoms that persist beyond the operative time [6,14] and extend beyond the work day [12]. Neuromusculoskeletal fatigue, impairment, and injuries have been shown to adversely affect MIS performance, patient safety, and surgeon career longevity [15][16][17][18][19][20]. The impact of suboptimal health on the ability of surgeons to perform quality MIS procedures is a major concern in hospitals worldwide [9,[21][22][23], prompting calls by medical practitioners and human factors engineers to request modification of the "hostile" and "dangerous" environment encountered by MIS surgeons [9,10,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The study also found that, during an 8-year period, there was an increase in psychiatric morbidity (from 22 to 33%), an increase in burnout (from 27 to 41%), and a decrease in job satisfaction (from 68 to 65%) (10). In the UK, surgeons were shown to exhibit susceptibility to substance abuse, sharps injuries, stress and burnout, and musculoskeletal pain (11). A Korean study demonstrated that, compared with other professions, surgeons were more prone to occupational stress.…”
Section: Introductionmentioning
confidence: 99%